## Trending News

# MATH POLYNOMIALS?

Multiply this please im confused. I would love if it has an explanation with it :)

1. (X+3)(x-1)(x+2)

2. (X^4+3x^2-1)(4x^3+x^2-x+3)

Thank you soo much

### 5 Answers

- mizooLv 75 years ago
1. (x + 3)(x - 1)(x + 2)

first working on (x + 3)(x - 1) we have :

= [x * (x - 1) + 3 * (x - 1)] * (x + 2)

= (x^2 - x + 3x - 3) * (x + 2)

Add like terms :

= (x^2 + 2x - 3) * (x + 2)

= x^2 * (x + 2) + 2x * (x + 2) - 3 * (x + 2)

= x^3 + 2x^2 + 2x^2 + 4x - 3x - 6

= x^3 + 4x^2 + x - 6

Here you can find some great examples http://www.mathsisfun.com/algebra/polynomials-mult...

- sepiaLv 75 years ago
1).

(x + 3)(x - 1)(x + 2)

= (x + 3)(x^2 + x - 2)

= x(x^2 + x - 2) + 3(x^2 + x - 2)

= x^3 + x^2 - 2x + 3x^2 + 3x - 6

= x^3 + 4x^2 + x - 6

2).

(x^4 + 3x^2 - 1)(4x^3 + x^2 - x + 3)

= x^4 (4x^3 + x^2 - x + 3) + 3x^2 (4x^3 + x^2 - x + 3) - (4x^3 + x^2 - x + 3)

= 4x^7 + x^6 - x^5 + 3x^4 + 12x^5 + 3x^4 - 3x^3 + 9x^2 - 4x^3 - x^2 + x - 3

= 4x^7 + x^6 + 11x^5 + 6x^4 - 7x^3 + 8x^2 - 3

help me too

- Login to reply the answers

- cidyahLv 75 years ago
1.

(x+3)(x-1) = x^2-x+3x-3 = x^2+2x-3

(x^2+2x-3)(x+2) = x^3+2x^2-3x+2x^2+4x-6

(x+3)(x-1)(x+2) = x^3+4x^2+x-6

2.

(x^4+3x^2-1)(4x^3+x^2-x+3)

= 4x^7+x^6-x^5+3x^4

+ 12x^5+3x^4-3x^3+9x^2

-4x^3-x^2+x-3

= 4x^7+x^6+11x^5+6x^4-7x^3+8x^2+x-3

help me too

- Login to reply the answers

- ThomasLv 75 years ago
(x+3)(x-1)(x+2) start by multiplying the first two parenthetical statements

(x+3)(x-1) which while you are multiplying is

x*x+-1*x+3*x+3*-1 which is just x^2+3x-x-3 grouping like terms leaves

(x^2+2x-3) which still needs to by multiplied by (x+2) which is:

x^2*x+2x*x-3*x+2*x^2+2*2x+2*-3 which is

x^3+2x^2-3x+2x^2+4x-6 grouping like terms...

x^3+4x62+x-6

help me too

- Login to reply the answers

- How do you think about the answers? You can sign in to vote the answer.

help me too